Development of Theragnostic Tool Using NIR Fluorescence Probe Targeting Mitochondria in Glioma Cells - Chu, Yeonjeong; Shin, Min Chul; Sung, June; Park, Jongmin; Kim, Eunha; Lee, Sanghee (AMER CHEMICAL SOC, 2019)
Because mitochondria are essential organelles for regulating energy homeostasis and intrinsic apoptosis, the perturbation of mitochondrial functions has been considered as an anticancer treatment. In this study, a new near-infrared (NIR) fluorescent probe, SiR-Mitol 1 was developed as a theragnostic agent for brain tumor by targeting mitochondria. SiR-Mito11 exhibited potential anticancer activity against glioma cells but tolerance in normal neuronal cells. We further confirmed that the selective accumulation of SiR-Mitol 1 in glioma cells disrupted mitochondria membrane potential, followed by apoptotic cell death.
Keywords: CANCER; APOPTOSIS; DELIVERY; BIOLOGY; RELEASE